Contemporary nutrition-based interventions to reduce risk of infection among elderly long-term care residents: A scoping review. - Athanasios Psihogios; Claudia Madampage; Brent E Faught (PLoS ONE)
Background Elderly long-term care residents (ELTCRs) face considerable burden of infection, especially evident during the COVID-19 pandemic. The nutritional status of the host can influence susceptibility to infection by altering immune system integrity, therefore, nutrition-based interventions may be a viable complement to existing infection prevention measures. Objective This scoping review sought to identify nutritional interventions and factors that have the strongest evidence to benefit ELTCRs, and thus best poised for rigorous clinical trial evaluation and subsequent implementation. Methods A database search of OVID-Medline, OVID-Embase, and Web of Science was performed from 2011 to 2021 to identify nutritional intervention studies which attribute to changes in infection in contemporary ELTCR settings. Articles were screened in duplicate and data extraction completed by a single reviewer, while a second reviewer verified the data which was fitted to identify evidence for nutritional interventions related to reducing rates of infection among ELTCRs. Results The search identified 1018 studies, of which 11 (nine clinical trials and two observational cohort studies) satisfied screening criteria. Interventions that significantly reduced risk of infection included whey protein (any infection), Black Chokeberry (urinary tract infection), and vitamin D (acute respiratory tract infection, skin and soft tissue infection). Both zinc and a dedicated meal-plan significantly improved lymphocyte parameters. Vitamin D deficiency was associated with the development of respiratory tract infections. Probiotic and soy-based protein interventions did not significantly affect risk of infection or lymphocyte parameters, respectively. Conclusion The current scoping review was effective in identifying the use of nutrition-based interventions for infection prevention among ELTCRs. In this study, some nutrition-based interventions were observed to significantly influence the risk of infection among ELTCRs. Nutritional interventions such as vitamin D (preventing deficiency/insufficiency), Black Chokeberry juice, zinc gluconate, whey protein, and varied and nutrient dense meal plans may be suitable for future rigorous clinical trial evaluation.